A Simple and Fast Computation Equivalent Circuit Model to Investigate the Effect of Tape Twisting on the AC Loss of HTS Cables - Sadeghi, A.; Seyyed Barzegar S. Μ.; Yazdani-Asrami, M. (Engineering, Technology & Applied Science Research, 2022)
This paper aims to evaluate the AC loss of a High Temperature Superconducting (HTS) cable with respect to the twisting angle while considering mechanical constraints in an iterative approach. A 1km 22.9kV AC HTS cable was selected in this study to assess the impact of the twisting angle alterations. The electromagnetic behavior of the selected HTS cable was modeled using an Equivalent Circuit Model (ECM). After the implementation of this model in MATLAB/SIMULINK, a series of simulations were performed without the consideration of mechanical limits. They showed that the increase in the twisting angle leads to the decrease of the AC loss. Afterwards, simulations were conducted to reduce the AC loss, while mechanical limits were taken into account. This improvement could reduce the AC loss by 27.41% with a much lower computation time than Finite Element Methods (FEMs).